2020
DOI: 10.1186/s12913-020-05187-5
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and predictors of organizational justice among healthcare professionals in academic hospitals in South-Eastern Nigeria

Abstract: Background: Research on organizational justice in hospitals in African countries are limited despite being important for workforce performance and hospital operational efficiency. This paper investigated perceptions and predictors of organizational justice among health professionals in academic hospitals in South-east Nigeria. Methods:The study was conducted in two teaching hospitals in Enugu State, South-east Nigeria using mixedmethods design. Randomly sampled 360 health professionals (doctors = 105, nurses =… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
3
6
0
1
Order By: Relevance
“…Even though nurses are one of the categories of healthcare professionals who provide actual medical services to patients, they tend to receive a relatively low wage compared to other healthcare professionals [ 3 ]. This correlates to the findings of previous studies that confirmed that the perceived organizational justice of nurses tended to be lower compared to that of other healthcare professionals, particularly doctors and pharmacists [ 34 ]. These findings suggest that nurses view their own compensation to be low given their working hours and the intensity of the work.…”
Section: Discussionsupporting
confidence: 90%
“…Even though nurses are one of the categories of healthcare professionals who provide actual medical services to patients, they tend to receive a relatively low wage compared to other healthcare professionals [ 3 ]. This correlates to the findings of previous studies that confirmed that the perceived organizational justice of nurses tended to be lower compared to that of other healthcare professionals, particularly doctors and pharmacists [ 34 ]. These findings suggest that nurses view their own compensation to be low given their working hours and the intensity of the work.…”
Section: Discussionsupporting
confidence: 90%
“…Even though a conducive working environment improves quality of nursing work life, the findings of this study highlighted several gaps in the work context which undermine the QWL and motivation of nurses. Nurses were blamed for most gaps in patient care, which is consistent with the blame culture found in prior studies [30] , [40] . Also, nurses lacked voice in the decision-making in private hospitals, as was found in other studies [6] , [20] , [32] .…”
Section: Discussionsupporting
confidence: 85%
“…The results of the study revealed the statistically significant correlations among age, years of experience and gender variables with total organizational justice. This is result supported by Ghasi et al, [66] revealed the statistically significant relationship for the age variable with organizational justice, whereas increasing age predicted a high perception of justice among nurses. While according to Aldhafri and Alsaidi, [67] no found statistical differences were found in organizational justice with years of experience among teachers.…”
Section: Results Regarding the Three Dimensions Of Organizationalsupporting
confidence: 71%